Unconventional approach in the study of diffusion welding of marine grades grey cast iron to low carbon steel - Bin Ayob, F. (Elsevier Ltd, 2019)
Experimental research on the joining of gray lamellar graphite cast iron with low carbon steel by diffusion welding is carried out with the expected result of establishing a methodology for the optimization of welding conditions producing the ultimate welding capacity of cast iron to low carbon steel. Preliminary studies on diffusion welding experiments have been carried out on the last few material specimens using a standard hot press. While some experiments failed to produce reliable joints, further inquiries into the unique characteristics of the equipment resulted in the necessary adjustments to parameters and procedures that resulted in successful joints. However, due to a sudden indefinite breakdown of the available standard machine/equipment led to the development of an alternative and unconventional approach for subsequent diffusion welding few experiments. This paper describes the experimental development of the alternative approach and equipment usage that produce a few diffusion couples. Â© 2019 Elsevier Ltd. All rights reserved.